2020
DOI: 10.1371/journal.pone.0239017
|View full text |Cite
|
Sign up to set email alerts
|

Mood-related behavioral and neurochemical alterations in mice exposed to low chlorpyrifos levels during the brain growth spurt

Abstract: Organophosphates are among the most used pesticides. Particularly, chlorpyrifos (CPF) is responsible for a number of deleterious effects on brain development, which may program behavioral changes later in life. Here, we investigated whether a regimen of early low level CPF exposure that did not result in a significant inhibition of acetylcholinesterase (AChE) had deleterious effects on mood-related behaviors, as well as on cholinergic and serotonergic biomarkers in the mice brain. From the 3 rd to 9 th postnat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…All of these findings indicate significant anxiety/depression-like behavior in pesticide-exposed F1 mice. These results are consistent with some studies of increased anxiety-like behaviors in mice, rats, and zebrafish exposed to CPF, 21 DDV, 80 and CP. 81 Epidemiological evidence suggests that CPF may affect the developing nervous system at low doses.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…All of these findings indicate significant anxiety/depression-like behavior in pesticide-exposed F1 mice. These results are consistent with some studies of increased anxiety-like behaviors in mice, rats, and zebrafish exposed to CPF, 21 DDV, 80 and CP. 81 Epidemiological evidence suggests that CPF may affect the developing nervous system at low doses.…”
Section: Discussionsupporting
confidence: 93%
“…A good body of literature has demonstrated that the development of the brain is particularly susceptible to exposure to various pesticides (e.g., OPPs), even at doses below the threshold for systemic toxicity. 21 The disruptions in the developing nervous system have been associated with altered cognition, impaired motor control, and behavioral deficits in rodents. 79 In the current study, we found that the mice exposed to pesticides spent less time and traveled shorter distances in the center zone, with more feces in the OFT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…altered activity and impulsivity [7][8][9]. Up to the present, related studies have provided sufficient evidence to show that there exists a strong link between CPF exposure, long-term persistent cognitive impairment and increased risk of neurodegenerative diseases [10,11].…”
Section: Agingmentioning
confidence: 83%
“…However, due to the low power of interactions at a given sample size relative to main effects, interactions at p < 0.1 were examined as to whether lower-order effects were detectable after subdivision of the interactive variables [ 44 ]. This criterion for interactions was used to identify interactive factors requiring subdivision for lower-order tests of effects of AIE and gabapentin [ 1 , 4 , 6 , 17 , 36 ]. There is no widespread agreement in the field on controlling for the False Discovery Rate when making planned comparisons or its effects on Type I error.…”
Section: Methodsmentioning
confidence: 99%